Implementation of Resolution No. 4/2016 of the ICPO-INTERPOL Concerning Biometric Data Sharing: Between Countermeasures Against Terrorist Foreign Fighters (FTFS) and Protection of the Privacy of Indonesian Citizens - Paripurna, Amira; Indriani, Masitoh; Widiati, Ekawestri Prajwalita (Brawijaya Law Journal, 2018)
This study aims to identify and explore the challenges in the implementation of Resolution No. 4/2016 of the ICPO-INTERPOL concerning sharing and exchanging biometric data among the members of ICPO-INTERPOL in order to counter terrorist foreign fighters (FTFs). This research also aims to elaborate and describe the mechanism of collecting, recording, storing, and exchanging biometric data conducted by the Indonesian government.The mechanism of collecting, recording, and storing biometric data works through 3 main doors, namely: 1) in the process of making electronic Resident’s ID Cards (e-ID Cards); 2) in the process of making SKCK (Certificates of Police Record); 3) in the process of making e-Passports. In the implementation of Resolution No. 4/2016 of ICPO-INTERPOL, the most obvious obstacles and challenges are the absence of regulations concerning the protection of personal data, and also the fact that the biometric data system itself is still relatively new and the database is not fully developed. Until today, the INTERPOL National Central Bureau (NCB) for Indonesia does not have its own biometric database system; instead they are using the database that is centralized at Pusinafis Polri (the Indonesian National Police’s Center of Automatic Fingerprint Identification System).The results of the study reveal that the biometric data recorded, collected, and stored are big data, but so far in supporting law enforcement and crime prevention processes the data have only been used as comparative data. In addition, there have also been found indications of violations of personal data and privacy, for example in relation to the absence of mechanism for data retention, consent, processing, notification, and disclosure.